2018
DOI: 10.1089/can.2018.0010
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Synergistic Interaction Between Cannabis-Derived Compounds for Cytotoxic Activity in Colorectal Cancer Cell Lines and Colon Polyps That Induces Apoptosis-Related Cell Death and Distinct Gene Expression

Abstract: Introduction: Colorectal cancer remains the third most common cancer diagnosis and fourth leading cause of cancer-related mortality worldwide. Purified cannabinoids have been reported to prevent proliferation, metastasis, and induce apoptosis in a variety of cancer cell types. However, the active compounds from Cannabis sativa flowers and their interactions remain elusive.Research Aim: This study was aimed to specify the cytotoxic effect of C. sativa-derived extracts on colon cancer cells and adenomatous polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 44 publications
3
47
0
Order By: Relevance
“…Synergistic interactions may be found between different cannabinoids ( i.e .,“intra-entourage”) [ 105 ] and between cannabinoids and terpenes ( i.e .,“inter-entourage”) [ 106 ]. Thus, cannabis appliance should be optimized to contain mixtures of these C. sativa -derived combined components.…”
Section: The “Entourage Effect” Of Cannabinoids and Terpenes For The mentioning
confidence: 99%
“…Synergistic interactions may be found between different cannabinoids ( i.e .,“intra-entourage”) [ 105 ] and between cannabinoids and terpenes ( i.e .,“inter-entourage”) [ 106 ]. Thus, cannabis appliance should be optimized to contain mixtures of these C. sativa -derived combined components.…”
Section: The “Entourage Effect” Of Cannabinoids and Terpenes For The mentioning
confidence: 99%
“…The SCBD extract was fractionated and 5 of the fractions that included HPLC-detected compounds were examined for cytotoxic activity ( Figure 1A). Following 48 h of treatment, fractions S4 and S5 were found to have high cytotoxic activity at 40 μg/mL (a relatively high concentration initially selected based on [19] to differentiate active from non-active fractions). Activity of S4 or S5 was ~12-and ~44-fold greater, respectively, than SCBD crude extract at 40 μg/mL and higher than doxorubicin at a concentration of 300 nM ( Figure 1B).…”
Section: High Cbd Cannabis Strain Extract and Fractions Of This Extramentioning
confidence: 99%
“…GC/MS analyses were carried out following [19], using a HP7890 gas chromatograph coupled to a HP6973 mass spectrometer with electron multiplier potential 2 KV, filament current 0.35 mA, electron energy 70 eV, and the spectra were recorded over 40 to 400 m/z. For concentration, 1 mg of each sample was dried under a gentle stream of nitrogen, and then dissolved in 6 mL of methanol prior to introduction to GC/MS.…”
Section: Gas Chromatograph (Gc) With Mass Selective Detector (Msd) (Gmentioning
confidence: 99%
See 1 more Smart Citation
“…1 − 3 More than 500 natural compounds belonging to a broad range of chemical classes have been identified or isolated from Cannabis . 4 , 5 The most abundant are the phytocannabinoids (plant-derived cannabinoids), a family of terpenophenolic compounds uniquely produced by the plant as secondary metabolites. 6 , 7 Gill et al, 8 showed that the activity of Δ 9 - trans -tetrahydrocannabinol (Δ 9 -THC), the primary active ingredient of Cannabis , is influenced by other compounds present in the plant, promoting the notion of phytochemical synergy in Cannabis pharmacology.…”
Section: Introductionmentioning
confidence: 99%